Humanitarian crises, intervention and security : a framework for evidence-based programming - Heyse, Liesbet, 1973- (2015)
"This book presents a new framework of analysis to assess natural and man-made disasters and humanitarian crises, and the feasibility of interventions in these complex emergencies. The past half-century has witnessed a dramatic increase in such crises - such as in Haiti, Iraq and Sudan - and this volume aims to pioneer a theory-based, interdisciplinary framework that can assist students and practitioners in the field to acquire the skills and expertise necessary for evidence-based decision-making and programming in humanitarian action. It has four major objectives: - To provide a tool for diagnosing and understanding complex emergencies, and build on the concepts of state security and human security to provide a 'Snap-Shot Analysis' of the status quo; - To provide a tool for analysing the causes of crises as well as the related stakeholder field; - To provide a frame to structure and analyse the information required to evaluate, monitor and/or design interventions for different actors on a project and/or programme level; - To combine concepts used in the humanitarian field with underlying theory in a practically relevant way. The book will be of much interest to students of humanitarian intervention, human security, peacebuilding, development studies, peace studies and IR in general"--
Includes bibliographical references (pages195-212) and index.
Keywords: Disaster relief; Decision making; Human services; Assistance in emergencies; Emergency management; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Peace